Antibiotic therapy of pneumonia - Dworacka, Marzena (Przewodnik Lekarza/Guide for GPs, 2007)
Antibiotic therapy in respiratory infections, especially treatment of pneumonia, is mostly empiric. Therefore many factors, except antimicrobial spectrum, including factors modyfying pharmacokinteic properties of antibiotics, co-existing diseases, patient’s age and diet should be considered. The proper antibiotics combinations and avoidance of the most frequent therapeutic errors are not less important. The term antibiotic therapy of pneumonia comprises also the currently recommended therapeutic schemes of community-acquired and hospital-acquired pneumonia which are briefly presented together with the examples of the dosage of some frequently used antibiotic